The Mediation Role of Psychological Immunity in the Association Between Loneliness and Subjective Well-Being Among University Students - Sanam, Zerlinda Christine Aldira; Subandi, Subandi (Utan Kayu Publishing, 2026)
Subjective well-being is a crucial indicator of positive psychological functioning among university students. However, loneliness remains a prevalent psychosocial issue in this population and is consistently associated with lower levels of subjective well-being. While previous studies have established a strong negative association between loneliness and subjective well-being, the psychological mechanisms underlying this relationship require further examination. This study aimed to investigate the mediating role of psychological immunity in the association between loneliness and subjective well-being among university students. Data were collected from 347 undergraduate students aged 18–25 years using standardized self-report measures assessing loneliness, psychological immunity, and subjective well-being. Mediation analysis revealed that loneliness was negatively associated with psychological immunity, while psychological immunity was positively associated with subjective well-being. Furthermore, psychological immunity partially mediated the relationship between loneliness and subjective well-being (indirect effect = −0.246, 95% CI [−0.395, −0.098]). These findings suggest that psychological immunity may represent an important internal psychological process linking loneliness and subjective well-being. The results highlight the potential value of strengthening psychological immunity as a target for interventions aimed at enhancing subjective well-being among university students experiencing loneliness.